Порівняльна характеристика природних та інтродукційних популяцій Bellevalia sarmatica (Pall. ex Georgi) Woronow, Hyacinthella leucophaea (C. Koch.) Schur, Muscari neglectum Guss. - Krivoruchko, T.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The results of comparative study of populations of Bellevalia sarmatica (Pall. ex Georgi) Woronow, Muscari neglectum Guss., Hyacinthella leucophaea (C. Koch.) Schur – species are rare within the region of the Poltava region in natural habitats and artificial steppe phytocenoses are presented. The main parameters of natural and introduced populations have been characterized. Modeling of the populations of rare plant species in artificial steppe ecosystems have been considered as a method of their ex situ protection.